Effect of nutritional counseling on low-density lipoprotein cholesterol among Thai HIV-infected adults receiving antiretroviral therapy. Issue 2 (1st February 2016) - Chotivichien, Saipin; Arab, Lenore; Prasithsirikul, Wisit; Manosuthi, Weerawat; Sinawat, Sangsom; Detels, Roger
ABSTRACT: HIV-infected patients receiving antiretroviral therapy have increased risk of metabolic syndrome, including dyslipidemia. In this study, we determined whether individual nutritional counseling reduced dyslipidemia, particularly low-density lipoprotein (LDL) cholesterol, among HIV-infected patients with dyslipidemia not currently taking lipid-lowering medication. We conducted a randomized 24-week trial among HIV-infected patients with dyslipidemia who were on antiretroviral therapy and were eligible to initiate therapeutic lifestyle changes according to the Thai National Cholesterol Education Program. Participants were randomly assigned to an intervention group that received individual counseling with a nutritionist for seven sessions (baseline, weeks 2, 4, 8, 12, 18, and 24) and a control group that received standard verbal diet information at baseline and nutritional counseling only at week 24. A 24-h recall technique was used to assess dietary intake for both groups at baseline and week 24. Lipid profile (total cholesterol, LDL, high-density lipoprotein (HDL), and triglyceride) was measured at baseline and after 12 and 24 weeks of therapy. An intention-to-treat and linear mixed model were used. Seventy-two patients were randomly assigned, and 62 (86%) participants completed their lipid profile test. After 12 weeks of follow-up, there were significant reductions in the intervention group for total cholesterol (−14.4 ± 4.6 mg/dL, P = .002), LDL cholesterol (−13.7 ± 4.1 mg/dL, P = .001), and triglyceride (−30.4 ± 13.8 mg/dL, P = .03). A significant reduction in LDL cholesterol was also observed in the control group (−7.7 ± 3.8 mg/dL, P = .04), but there were no significant differences in change of mean lipid levels between the groups at 12 weeks of follow-up. After 24 weeks, participants assigned to the intervention group demonstrated significantly greater decreases in serum total cholesterol (−19.0 ± 4.6 vs. 0.2 ± 4.3 mg/dL, P = .003) and LDL cholesterol (−21.5 ± 4.1 vs. −6.8 ± 3.8 mg/dL, P = .009). There were no significant changes in HDL cholesterol or triglyceride levels in either group.